Photocatalytic Hydrogen Production with Copper Photosensitizer–Titanium Dioxide Composites. Issue 1 (28th August 2013) - Karnahl, Michael; Mejía, Esteban; Rockstroh, Nils; Tschierlei, Stefanie; Luo, Shu‐Ping; Grabow, Kathleen; Kruth, Angela; Brüser, Volker; Junge, Henrik; Lochbrunner, Stefan; Beller, Matthias
Abstract A series of heteroleptic copper photosensitizers [( <![CDATA[PP]]> <inline-graphic xlink:href="ark:/27927/pgg4smt22m7" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />)Cu( <![CDATA[NN]]> <inline-graphic xlink:href="ark:/27927/pgg4smt1zg0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(SO3Na)2)]+ containing sulfonate anchor groups is described. In the presence of titanium dioxide they form composites, which are active photosensitizers in the light driven reduction of protons. Further stabilization of these systems is achieved by encapsulation within a plasma‐polymerized allylamine (PPAAm) layer. The resulting PPAAm‐CuPS‐TiO2‐composites exhibit a strong absorption in the visible region of the light. Photocatalytic hydrogen production is performed by using only non‐noble metals. In the presence of an iron reduction catalyst a maximum turnover number of 2452 is obtained.